PENGARUH METODE GUIDE NOTE TAKING TERHADAP PRESTASI BELAJAR MATEMATIKA - Amir, Almira (Logaritma : Jurnal Ilmu-ilmu Pendidikan dan Sains, 2015)
In general the low learning achievement of students due to the problems that arise in the learning process. Seeing the reality of it is one of the important agenda for the teacher is to create is to create a learning environment in math. The achievement of learning achievement required an appropriate delivery methods that aim can empower students, both in terms of academic and social skills, and in the end students got knowledge, can understand the concepts being taught, and students can solve the problem with an open nature,Â  so that the porpuse of education can be achieved. Guide of note taking method is the correct method to improve students achievement in math. Guide note of taking method is a method that as fairly simple and fun which are used to aid students in making notes or important points when delivering course material will be provided.